2014
DOI: 10.1007/s00192-014-2442-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking behaviour and social status of women with pelvic organ prolapse, 4th-degree obstetric tears, and obstetric fistula in western Uganda

Abstract: This study confirms the social stigma associated with obstetric fistula, however also highlights the social stigma faced by women suffering with severe pelvic organ prolapse and unrepaired 4th degree obstetric tears in western Uganda. There is an urgent need for education and training in obstetric management and pelvic organ prolapse management in such areas of limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…[4][5][6] With women now accessing health care more frequently, the rates of caesarean section in general have increased, and the rates of caesarean section in women suffering OF are high, reaching well over 50%. 7,14 In our study, the group of women suffering OF had a caesarean section rate of 74.4%. Despite these extremely high rates of caesarean section in women with OF, stillbirth remains the most frequent outcome in over 70% of cases 8,14 and OF from pressure necrosis persists.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[4][5][6] With women now accessing health care more frequently, the rates of caesarean section in general have increased, and the rates of caesarean section in women suffering OF are high, reaching well over 50%. 7,14 In our study, the group of women suffering OF had a caesarean section rate of 74.4%. Despite these extremely high rates of caesarean section in women with OF, stillbirth remains the most frequent outcome in over 70% of cases 8,14 and OF from pressure necrosis persists.…”
Section: Discussionmentioning
confidence: 53%
“…3 While earlier literature indicates that vaginal delivery is the most common mode of delivery for women who suffer genital tract fistulae from obstructed labour, [4][5][6] more recent surveys demonstrate high rates of caesarean section deliveries for these women who develop fistulae. [7][8][9] Even when delivered by caesarean section, the majority of women with OF experience a stillbirth. 1,8,9 Thus, caesarean section is now commonly performed in women with intra-uterine fetal death with obstructed labour.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is a shortage of reliable data around social, demographic and clinical factors associated with time to recovery from obstetric Fistula surgical repair that will be valuable for managing health care institution through planning, monitoring and evaluation of quality of care as well as use of human and material resources [29][30][31][32][33][34][35].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Women with pelvic floor dysfunction (PFD)—including obstetric fistula, unrepaired obstetric anal sphincter injuries (OASIS), or severe pelvic organ prolapse (POP; defined as stage 3 or 4)—can experience high levels of social stigma and social isolation . This observation suggested that PFD might be a risk factor for IPV.…”
Section: Introductionmentioning
confidence: 99%